Induction Of Hairy Root Cultures From Difficult-To-Transform Eurycoma Longifolia (Tongkat Ali) Using Wild Strains Of Agrobacterium Rhizogenes With Antibacterial Studies - Danial, Monica (2011)
Production of hairy roots from the difficult-to-transform medicinally important plant Eurycoma longifolia will ensure continuous supply of secondary metabolites and thus minimizes the harvesting of this plant from the wild. Seed morphology and histology analysis of Eurycoma longifolia by light microscopes revealed seeds structures of this important medicinal plant at different growing stages. The seed development phases and the development of the vascular system on the progression of germination provide the insight of the actual and accurate information on the cotyledon development period. Seeds being the storage organ may facilitate the generation of the hairy roots, as it evidently has the essential features like tracheas, which are the main site of infection for Agrobacterium rhizogenes. Chemotaxis using the swarm agar plate method initiates the process of bacterial infection towards the plant cells and thus conferring beneficial attributes to the host. Strong positive chemotactic response was observed in most of the tested bacteria strains towards the in vitro root and somatic embryos. Hairy roots were successfully initiated using three wild strains of Agrobacterium rhizogenes namely MAFF 210265, MAFF 301726 and MAFF 720002 at the hypocotyls region of Eurycoma longifolia. Amplification of the rol gene at 1100bp by PCR analysis confirmed the T-DNA integration of the Ri plasmid in the hairy roots. In addition, the antibacterial assay conducted for the in vivo plant parts of Eurycoma longifolia using disc diffusion method reveals that the crude extract obtained from the roots, possesses the highest amount of the antibacterial substance that works well with the most of the tested pathogenic bacteria like Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853, Bacillus cereus ATCC 10876, Staphylococcus aureus ATCC 25923, Shigella flexneri ATCC 12022 and Bacillus subtilis (CDR). Thus, the many beneficial properties of Eurycoma longifolia makes it an ideal plant to be researched and studied extensively. Generating hairy roots in Eurycoma longifolia will be highly beneficial to the pharmaceutical industry with valuable secondary metabolites, which is directly linked to its root differentiation at a low biomass starting material.